Redesain Environmental Graphic Taman Bungkul Surabaya dengan Teknik Vektor sebagai Upaya Optimalisasi Media Informasi - Mukadar, Winda Tri Astami; Bahruddin, Muh; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2016)
Taman Bungkul of Surabaya is one of the city parks that have a very important role for the development of Surabaya city as evidenced with being visited by their local travelers even foreign tourists. To make tourists understand more about the available facilities, it required a precise information media. The Information Media being said is containing the form of environmental graphic design such as sign system and wayfinding inside the park. In this scheme, the data has been obtained and analyzed by using multiple stages, namely data reduction stage, data presentation, and conclusion. After analyzing the data, we've discovered a design concept or a keyword which is